Biohybrid generators based on living plants and artificial leaves: influence of leaf motion and real wind outdoor energy harvesting. (13th August 2021) - Meder, Fabian; Armiento, Serena; Naselli, Giovanna Adele; Thielen, Marc; Speck, Thomas; Mazzolai, Barbara
Abstract: Plants translate wind energy into leaf fluttering and branch motion by reversible tissue deformation. Simultaneously, the outermost structure of the plant, i.e. the dielectric cuticula, and the inner ion-conductive tissue can be used to convert mechanical vibration energy, such as that produced during fluttering in the wind, into electricity by surface contact electrification and electrostatic induction. Constraining a tailored artificial leaf to a plant leaf can enhance oscillations and transient mechanical contacts and thereby increase the electricity outcome. We have studied the effects of wind-induced mechanical interactions between the leaf of a plant (Rhododendron) and a flexible silicone elastomer-based artificial leaf fixed at the petiole on power output and whether performance can be further tuned by altering the vibrational behavior of the artificial leaf. The latter is achieved by modifying a concentrated mass at the tip of the artificial leaf and observing plant-generated current and voltage signals under air flow. In this configuration, the plant-hybrid wind-energy converters can directly power light-emitting diodes and a temperature sensor. Detailed output analysis has revealed that, under all conditions, an increase in wind speed leads to nearly linearly increased voltages and currents. Accordingly, the cumulative sum energy reaches its highest values at the highest wind speed and resulting oscillations of the plant-artificial leaf system. The mass at the tip can, in most cases, be used to increase the voltage amplitude and frequency. Nevertheless, this behavior was found to depend on the individual configuration of the system, such as the leaf morphology. Analysis of these factors under controlled conditions is crucial for optimizing systems meant to operate in unstructured outdoor scenarios. We have established, in a first approach, that the artificial leaf-plant hybrid generator is capable of autonomously generating electricity outdoors under real outdoor wind conditions, even at a low average wind speed of only 1.9 m s −1 .